Utility of Hyperbaric Oxygen Therapy for Acute Acoustic Trauma: 20 years' Experience at the Japan Maritime Self-Defense Force Undersea Medical Center - Oya, Morihiko; Tadano, Yutaka; Takihata, Yasuhiro; Ikomi, Fumitaka; Tokunaga, Tetsuji (International Archives of Otorhinolaryngology, 2019)
Introduction Acute acoustic trauma, which is a kind of sensorineural hearing loss, is caused by acoustic overstimulation. Hyperbaric oxygen therapy (HBOT) is reported to be effective against acute acoustic trauma.Objective We aimed to evaluate the efficacy of HBOT against acoustic hearing loss based on our 20 years of experience with such cases.Methods Patients who were treated with HBOT for acute acoustic trauma between April 1997 and August 2017 were evaluated in this study. Thirty-five patients with a mean age of 25.7 ± 9.2 (range: 16–48) years were included. Thirty-nine out of 70 ears (35 patients) were damaged. We investigated the initial level of hearing loss; the extent to which hearing recovered; subjective symptoms, such as tinnitus and aural fullness; and the treatment administered.Results The planned HBOT was completed in 37 of 39 ears. Twenty-six of the 37 ears (70.2%) displayed improved hearing, and 31 of the 37 ears (83.9%) exhibited symptom improvement. Twenty-three (76.7%) and 26 (86.7%) of the 30 ears treated with steroids demonstrated improvements in hearing and subjective symptoms, respectively.Conclusion A combination of HBOT and steroids should be considered as a treatment for acute acoustic trauma in cases involving symptoms such as tinnitus and aural fullness.
Keywords: HBOT; sensorineural deafness; tinnitus